Two New Species of the Genus Longipedia Claus, 1863 (Copepoda: Harpacticoida: Longipediidae) from Korea, with an Update and a Key to Species - Hyun Woo Bang (MDPI AG, 2021)
Benthic harpacticoids were collected from Korean waters. Two species were identified as members of the genus Longipedia Claus, 1863, because they have an extremely elongated distal segment of the P2 endopod. Longipedia koreana sp. nov. is morphologically most closely related to L. nichollsi Wells, 1980 and L. scotti Sars, 1903, but it can clearly be distinguished from both species based on the following morphological characteristics: P1 coxa with strong spinules near the outer margin and the distal element being much bigger than the proximal elements, P2 coxa with a small inner seta on the anterior surface, P4 exopod first segment without an inner element, and the P5 with a rectangular exopod (more than 3.5 times as long as wide). L. ulleungensis sp. nov. is similar to L. brevispinosa Gurney, 1927, L. spinulosa Itô, 1981, and L. weberi Scott A., 1909. However, L. ulleungensis sp. nov. is characterized by the P2 coxa with a reduced inner seta, the P4 exopod second segment without an inner seta, and the anal operculum with a long median projection, a single spine, and a group of outer spines on each side. In a molecular analysis using the mitochondrial cytochrome c oxidase subunit I (COI) and 18S ribosomal RNA (18S rRNA) genes, the inter-specific variation was 22.525–23.102% and 1.325–1.382% of COI and 18S rRNA between the two new species, respectively. A key to the family Longipediidae is provided herein.